2012
DOI: 10.1007/s11434-012-5177-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ U-Pb dating of titanite by LA-ICPMS

Abstract: Titanite is an ideal mineral for U-Pb isotopic dating because of its relatively high U, Th and Pb contents. Here, we developed a technique for U-Pb dating of titanite using the 193 nm ArF laser-ablation system and Agilent 7500a Q-ICP-MS. Standards of titanite (BLR-1 and OLT-1) and zircon (91500 and GJ-1) were dated using single spot and line raster scan analytical methods. To check the matrix effect, titanite (BLR-1) and zircon (91500) standards were analyzed as the external standards. The weighted mean 206 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 38 publications
(92 reference statements)
1
37
0
1
Order By: Relevance
“…As both titanite and allanite are silicates, we decided to use the GJ-1 zircon as the primary standard. As already explained in Fallourd et al (2014), Sun et al (2012) claimed that titanite can be up to 12 % younger than their known ages using either spot or raster analyses when a zircon standard is used. However, Storey et al (2006) and Darling et al (2012) concluded that the error related to the non-matrix matching between the unknown (titanite and allanite, respectively) and the external standard (zircon) is negligible.…”
Section: U-th-pb Methodsmentioning
confidence: 96%
“…As both titanite and allanite are silicates, we decided to use the GJ-1 zircon as the primary standard. As already explained in Fallourd et al (2014), Sun et al (2012) claimed that titanite can be up to 12 % younger than their known ages using either spot or raster analyses when a zircon standard is used. However, Storey et al (2006) and Darling et al (2012) concluded that the error related to the non-matrix matching between the unknown (titanite and allanite, respectively) and the external standard (zircon) is negligible.…”
Section: U-th-pb Methodsmentioning
confidence: 96%
“…Titanite is also very common in many nephrite deposits (Cooper, 1995;Ling, 2012;Liu et al, 2010;Lu, 2005;Qin, 2013;Simandl et al, 1999;Tao, 1992). Recent studies demonstrated that titanite U-Pb age determination using modern microbeam techniques (SIMS and LA-ICPMS) has great potential to provide robust constraints on the timing of highto intermediate-grade metamorphism (Li et al, 2014;Rasmussen et al, 2013;Sun et al, 2012). In this study, we present SIMS U-Pb titanite age data for the Luanchuan nephrite deposit in Central China.…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation and analytical method for titanite U–Pb dating followed those described by Sun et al . (). The ICP‐MS measurements were carried out using time‐resolved analysis.…”
Section: Methodsmentioning
confidence: 99%